Phenolic content and antioxidant activities of Vitis vinifera L. leaf extracts obtained by conventional solvent and microwave-assisted extractions - Djemaa-Landri, Kenza; Hamri-Zeghichi, Sabrina; Valls, Josep; Cluzet, Stéphanie; Tristan, Richard; Boulahbal, Nawel; Kadri, Nabil; Madani, Khodir (Université de Bouira, 2020)
Grapevine leaves are used in the cuisines in the countries surrounding the Mediterranean and in folk medicine. They contain a huge amount of phenolic constituents. To optimize the extraction of bioactive compounds present in grapevine leaves, two methods of extraction were compared: conventional solvent extraction (CSE) and microwave-assisted extraction (MAE). The optimal extraction conditions in term of total phenolic content (TPC) were determined using a Box–Behnken design (BBD) from leaves of Vitis vinifera L. cv. Le tizourine Bou Afraraet. Optimal extraction conditions for CSE was 29% concentration of ethanol (v/v), 30.96 min extraction time, and 72:1 liquid-to-solid ratio (mL:g), at 37.5 °C. For MAE it was 34% concentration of ethanol(v/v), 474 W microwave power, 47 s irradiation time and 40:1 liquid-to-solid ratio (mL:g). Both extracts obtained by optimized MAE and CSE processes were compared in terms of total flavonoid content (TFC) and antioxidant activities (DPPH, ORAC, PFRAP and ICA). The MAE extract exhibited highest phenolic content and antioxidant activities. Moreover, phenolic compounds from leaves of Vitis vinifera L. cv. Ahmar-Bou-Amar were extracted following MAE optimal conditions and compared to Le tizourine Bou Afraraet extract. In addition to TPC and antioxidant activities, phenolic constituents were determined using HPLC–DAD-IT-MS and UPLC-QqQ-MS/MS. A total of sixteen phenolic compounds were identified and quantified including two phenolic acids, seven flavonols, three flavanols and four stilbenes. The obtained data revealed that the leaves of two native Algerian grapevines are rich in bioactive constituents, and can constitute by-products with added-value for food supplements.
Keywords: Grapevine leaves; Polyphenols; Microwave-assisted extraction; Optimization; Antioxidant activity